2012
DOI: 10.1177/1079063212459086
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Recidivism Among Juveniles Who Have Offended Sexually

Abstract: Literature on risk factors for recidivism among juveniles who have sexually offended (JSOs) is limited. In addition, there have been no studies published concerning protective factors among this population. The purpose of this study was to examine the relationship of risk and protective factors to sexual and nonsexual recidivism among a sample of 193 male JSOs (mean age = 15.26). Youths were followed for an average of 7.24 years following discharge from a residential sex offender treatment program. The risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 60 publications
2
29
2
9
Order By: Relevance
“…The findings of the current study support the results previously reported by Spice et al (2013). In their study, no protective factor of the SAVRY was associated with sexual recidivism.…”
Section: Discussionsupporting
confidence: 94%
“…The findings of the current study support the results previously reported by Spice et al (2013). In their study, no protective factor of the SAVRY was associated with sexual recidivism.…”
Section: Discussionsupporting
confidence: 94%
“…For example, Spice et al (2012) found that the SAVRY-protective factor Strong attachments and bonds had a small but statistically significant negative correlation with nonviolent recidivism but not with sexual recidivism in their sample of 193 adolescents with sexual offenses. There simply is insufficient empirical work yet to draw firm conclusions about which constructs and measures of protective factors should be incorporated into comprehensive risk assessments with this population.…”
Section: Discussionmentioning
confidence: 95%
“…This sample of youth has been included in previous research on risk and protective factors (Elkovitch, Viljoen, Scalora, & Ullman, 2008; Latzman, Viljoen, Scalora, & Ullman, 2011; Spice, Viljoen, Latzman, Scalora, & Ullman, 2013; Viljoen, Elkovitch, Scalora, & Ullman, 2009; Viljoen et al, 2008). However, the current study has a different focus (i.e., dynamic change) and does not include any analyses that are redundant with prior work.…”
Section: Methodsmentioning
confidence: 99%